Medicaid Costs Associated with the Hospitalization of - Michael J. Kanellis, DDS, MS; Peter C. Damiano, DDS, MPH; Elizabeth T. Momany, PhD (Blackwell Synergy, 2000)
This paper examines the cost to the Iowa Medicaid program of hospitalizing young children for restorative den fa1 care under general anesthesia, and describes the dental services received in this setting